(untitled) (Informatica, 2024)
As organizations employ technology to change their business operations into something simpler, quicker, more secure, adaptable, and lucrative, digital transformation is assisting them in doing so. Cloud computing technology is a cornerstone to this transformation. Cloud computing imparts a more affordable, scalable, and location-independent platform for handling client data. Customers may benefit from the advantages of this new paradigm by outsourcing compute and storage requirements to public providers and paying for the services consumed. Cloud computing bestows advantageous on-the-demand oriented network ingress to specific a pool of adjustable computing resources that may be shared and which can be promptly deployed with better minimum management and efficiency oriented overhead. Cloud paradigm provides the prime and fundamental benefit of computation oriented outsourcing, where due to customers are no longer confined by their resource-constrained devices thanks to the cloud’s computing capabilities. Outsourcing allows you to save time and money. With the outsourcing problem to cloud, clients can always get the benefits of limitless computational resources in pay and use manner, free from software and hardware maintenance and operational overhead related concerns. Traditional encryption as a solution protects privacy, but restricts future data usage, reducing the fundamental economic benefits of using public cloud services dramatically. Processing on encrypted data is widely acknowledged research problem in cryptography. We offer a secure system in this study and an oracle for query vectors outsourcing using privacy homomorphism. The empirical analysis for the proposed prototype in terms of computational and security aspects, experiment results discussion is also given in this paper.